KAJIAN PENGGUNAAN WHEY BUBUK SEBAGAI PENGGANTI SUSU SKIM BUBUK DALAM PENGOLAHAN SOFT FROZEN ES KRIM - M. E. Sawitri; A. Manab; M. Huda (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2010)
The objectives of this research were to determine effect of substitution level of skim milk powder with whey powder on the quality of soft frozen ice cream and as an information for practician and industry related the research product. The materials of the research were soft frozen ice cream, the treatment were substitution levels of skim milk powder with whey powder (w/w) :W0 (0%), W1 (25%), W2 (50%), W3 (75%) and W4 (100%) from solid non fat. The research method was an experiment using Randomized Block Design, with three replication. The variables measured were the overrun, melting rate, and organoleptic quality of soft frozen ice cream. Data were analyzed by analysis of variance and followed by Duncan’s Multiple Ranger Test. The result of the research showed that substitution level of skim milk powder with whey powder gave a highly significant effect (P<0,01) on overrun, melting rate and organoleptic quality of soft frozen ice cream. The substitution of skim milk powder with whey powder 75% (w/w) gave the best quality of soft frozen ice cream according to the SNI which had 10% fat, 13% of sugar and 36% of solid. (JIIPB 2010 Vol 20 No 1: 31-37).   Keywords : whey powder, skim milk powder, soft frozen ice cream